The Influence of Employee Performance on the Quality of Public Services: A Study at the Office of the South Morotai Subdistrict, Morotai Island Regency - Hasan, Jamiludin; Umar, Ardin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to determine the effect of employee performance on the quality of public services. A sample of 52 respondents was used. The tests used included instrument testing, data testing, and simple regression. Data collection techniques in this study involved distributing questionnaires. The data obtained were then analyzed qualitatively, including validity and reliability tests, and simple regression tests. The results indicate that employee performance influences service quality. This is evidenced by a comparison of the t-table values, where the calculated t-value is greater than the predetermined t-table.